Māturīdite Kalam among Southeast Asian Ash`Arite: A Synthesis of Māturīdite Influences on Dayah’s Theology - Saifuddin Dhuhri; Tarmizi Jakfar (Al-Jami'ah: Journal of Islamic Studies, 2020)
As the earliest Muslims and first known who introduced Islam in Southeast Asia, Dayah community has continuingly played a great role in retaining and spreading the Ash`arite school of theology in the region. Ash`arite theology is a major area of interest within the field of Islamic studies in Southeast Asia. The teachings of Māturīdite kalam have, however, received little attention, in particular its impact on local theology from many scholars. Furthering the legacy of Nasafi’s construction of Southeast Asian theology, this paper is an attempt to unearth Māturīdi’s significance among Southeast Asian Muslims by analyzing the content of dayah’s curriculum, explaining the intellectual network of Māturīdite ulema, and explicating the role of Ahlu al-Sunnah wa al-Jamaah consensus along with interviewing several key informants on the issues of Islamic theology. I craft this paper by arguing that Māturīdite kalam has considerable impacts on local theology, e.g., upholding rationality on God’s attributes, and relying on ilm mantiq method in justifying human freedom. This paper has great contributions in advancing the study of Southeast Asian Muslim theology and its relation to the concept of Islamisation of indigenous culture; like the concepts of cosmopolitanism and syncretism, and the finding of Māturīdi’s kalam in Southeast Asia.[Dayah di Aceh, institusi yang paling awal mengenalkan Islam di Asia Tenggara, hingga saat ini masih merupakan aktor yang berperan penting dalam mempertahankan dan menyebarkan mazhab Ash’ariyah di kawasan ini. Mazhab ini juga dominan dalam kajian Islam di Asia Tenggara. Pengajaran ilmu kalam Māturīdiah, meski mendapat porsi sedikit, pada khususnya berpengaruh pada teologi para ulama setempat. Artikel ini bertujuan untuk menggali signifikasi Māturīdiah dikalangan muslim Asia Tenggara melalui analisis materi kurikulum pengajaran di dayah, pemetaan jaringan ulama Māturīdiah dan mengurai peran konsensus para Aswaja. Dengan wawancara beberapa tokoh kunci dayah di Aceh, tulisan ini menunjukkan bahwa ilmu kalam Māturīdiah berpengaruh pada teologi lokal seperti; dukungan rasionalitas dalam mengenal Tuhan dan mempertimbangkan metode ilmu mantiq dalam pembenaran kebebasan manusia. Artikel ini mempunyai kontribusi penting dalam kajian teologi Islam di Asia Tenggara dan hubungan antar konsep dalam islamisasi budaya lokal seperti kosmopolitanisme, sinkretisme, dan teologi Māturīdi.]